Analysis A Criminological Study of Supreme Court Decision No. 574K/PID.SUS./2018 on the Criminalization of a Sexual Harassment Victim Resulting in a Conviction, Reviewed under Law Number 12 of 2022 on Sexual Violence Crimes - Sumansyah, Riki; Maryani, Desy; Pase, Ana Tasia (JURNAL HUKUM SEHASEN, 2026)
The Supreme Court Decision Number 574 K/Pid.Sus./2018 has generated controversy as it is considered to have criminalized a victim of sexual harassment who was ultimately convicted as a defendant. This decision reflects serious problems in the enforcement of criminal law, particularly in relation to the protection of victims of sexual violence. This study aims to examine the decision from a criminological perspective and to review it based on Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS). The research method employed is normative legal research using a statutory approach, a case approach, and a conceptual approach. The data are derived from primary, secondary, and tertiary legal materials and are analyzed qualitatively. The findings indicate that the Supreme Court decision has not fully reflected the principles of victim protection and restorative justice as mandated by the UU TPKS. From a criminological perspective, the criminalization of victims has the potential to cause secondary victimization and to reinforce a culture of fear in reporting cases of sexual violence. Therefore, a paradigm shift among law enforcement officials is necessary in handling sexual violence cases to ensure alignment with the spirit of victim protection and respect for human rights as stipulated in the UU TPKS